2013
DOI: 10.1007/s10495-013-0867-x
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol inhibits osteoblast apoptosis via promotion of autophagy through the ER–ERK–mTOR pathway

Abstract: Estradiol could protect osteoblast against apoptosis, and apoptosis and autophagy were extensively and intimately connected. The aim of the present study was to test the hypothesis that autophagy was present in osteoblasts under serum deprivation and estrogen protected against osteoblast apoptosis via promotion of autophagy. MC3T3-E1 osteoblastic cells were cultured in a serum-free and phenol red-free minimal essential medium (α-MEM). Ultrastructural analysis, lysosomal activity assessment and monodansycadaver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 48 publications
7
98
1
Order By: Relevance
“…Consistent with previous reports [19,52], Baf A actually increased the autophagy incidence and elevated the expression of LC3 II/I in our study, although it is an autophagy inhibitor. The proper explanation was that Baf A inhibited the fusion of autophagosomes/lysosomes and decreased the autophagic degradation, thus blocking the downstream step in the autophagy flux.…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with previous reports [19,52], Baf A actually increased the autophagy incidence and elevated the expression of LC3 II/I in our study, although it is an autophagy inhibitor. The proper explanation was that Baf A inhibited the fusion of autophagosomes/lysosomes and decreased the autophagic degradation, thus blocking the downstream step in the autophagy flux.…”
Section: Discussionsupporting
confidence: 94%
“…Wong et al [28] reported that ROS-dependent ERK induced non-canonical autophagy in cancer cells. As the down-stream kinase of ERK, the inhibition of p-mTOR has consistently been associated with induction of autophagy [69]. Our results showed that H 2 O 2 treatment inactivated mTOR and reduced phosphorylation of its downstream target p70S6K, corresponding to the variation of autophagy.…”
Section: Discussionmentioning
confidence: 57%
“…57 It has also been reported that estrogen inhibits osteoblast apoptosis in vitro, inducing autophagy in these cells. 58 Autophagy is also essential when osteoblasts are incorporated into the bone matrix, thus becoming osteocytes. 59 During the transition, osteoblasts undergo evident changes in their shape, accompanied by a significant reduction in the number and size of organelles.…”
Section: Role Of Autophagy In Bone Biologymentioning
confidence: 99%